Gambaran Tingkat Pengetahuan Obat Generik di Kalangan Mahasiswa STIKES ISFI Banjarmasin Tahun 2022 - Aulia Rahim; Riza Alfian; Shafaa Dhiya; Yugo Susanto; Mochammad Maulidie Alfianoor Saputera (HB PRESS, 2022)
Generic drugs are drugs with the official name International Nonproprietary Names (INN) which are stipulated in the Indonesian Pharmacopoeia or other standard books for the efficacy substances they contain. Generic drugs are often considered low-quality drugs because of their affordable price. The lack of public knowledge about generic drugs is the main factor that makes these drugs underutilized. As prospective pharmacists, pharmacy students are responsible for providing drug information. The purpose of this research was to understand the level of students of STIKES ISFI Banjarmasin regarding generic drugs. The type of this research was non-experimental using a cross-sectional design. The gathering of data used a questionnaire using Google Forms with the prospective method. The gathering of samples used the saturated sampling technique, namely all active students in STIKES ISFI Banjarmasin totaling 350 students, with inclusion criteria. The data were analyzed using Microsoft Excel and SPSS, then presented in a form of a table. The result of the level of generic drugs knowledge research among the STIKES ISFI Banjarmasin student was obtained with the high understanding category as many as 186 respondents (53.14%), moderate as many as 146 respondents (41.72%), low understanding as many as 18 respondents (5.14%) and with an average of understanding from 350 respondents including good category with 76.63% of right answers.